Ein Rahmenwerk für die Architektur von Frühwarnsystemen (2017)
Early warning systems are supposed to deliver information about an emerging threat in order to allow persons and organizations to react accordingly. The design of an early warning system presents complex challenges to the system architects. For this, the present work provides a framework for the architecture of future early warning systems. Particular attention is paid to solve various architectural problems by means of semantic technologies and the automation of workflows.